Building Information Modelling adoption in the European Union: An overview. (September 2019) - Charef, Rabia; Emmitt, Stephen; Alaka, Hafiz; Fouchal, Farid
Abstract: Building information modelling (BIM) is one of the most promising recent developments in the Architecture, Engineering, Construction and Operation (AECO) industry. However, its adoption remains a challenge for the AECO industry because it requires a shift to a new way of working, leading to a current discrepancy in the adoption of BIM in the EU. The paper aims at assessing the gaps in the BIM adoption between the 28 EU countries and the barriers related to its implementation. The methodology adopted here is twofold: first, secondary data are given by a systematic literature review, completed with the review of current projects funded by the European Commission, and dealing with fostering the BIM adoption. Second, primary data are provided by a questionnaire survey to classify BIM initiatives regarding policies, the level of adoption and the barriers encountered in the 28 EU countries. In order to grade the heterogeneity of BIM adoption in the EU, we have classified the countries into four categories with different levels of awareness, from early adopters (BIM already mandated) to countries without any plan. The survey has enabled the analysis of twenty barriers to BIM adoption using the four grades in relation to the respondent country. We found barriers that are acknowledged by all countries irrespective of their level of BIM adoption. Other barriers have been already tackled by the early adopters but not by the newcomers who have yet to experience some of these issues. Finally, the assessment of the disparities of BIM adoption within the EU can help the European Commission towards unifying European standard on BIM. Highlights: A heterogeneity of BIM adoption in the EU is highlighted. Different levels of BIM awareness from early adopters to countries without any plan. Based on the literature and a questionnaire, BIM adoption barriers were identified and classified. Recommendations to foster the BIM adoption in the EU are proposed.